Health Data, Information, and Knowledge Sharing for Addressing the COVID-19 - Soualmia, Lina F.; Hollis, Kate Fultz; Mougin, Fleur; Séroussi, Brigitte (Yearbook of Medical Informatics, 2021)
Objectives: To introduce the 2021 International Medical Informatics Association (IMIA) Yearbook by the editors.Methods: The editorial provides an introduction and overview to the 2021 IMIA Yearbook whose special topic is “Managing Pandemics with Health Informatics - Successes and Challenges”. The Special Topic, the keynote paper, and survey papers are discussed. The IMIA President's statement and the IMIA dialogue with the World Health Organization are introduced. The sections’ changes in the Yearbook Editorial Committee are also described.Results: Health informatics, in the context of a global pandemic, led to the development of ways to collect, standardize, disseminate and reuse data worldwide: public health data but also information from social networks and scientific literature. Fact checking methods were mostly based on artificial intelligence and natural language processing. The pandemic also introduced new challenges for telehealth support in times of critical response. Next generation sequencing in bioinformatics helped in decoding the sequence of the virus and the development of messenger ribonucleic acid (mRNA) vaccines.Conclusions: The Corona Virus Disease 2019 (COVID-19) pandemic shows the need for timely, reliable, open, and globally available information to support decision making and efficiently control outbreaks. Applying Findable, Accessible, Interoperable, and Reusable (FAIR) requirements for data is a key success factor while challenging ethical issues have to be considered.
Keywords: Medical Informatic; health information technology; IMIA Yearbook of Medical Informatics; COVID-19; pandemic